Power system joint energy and reserve scheduling model considering variable speed pumped hydro storage for mitigating wind curtailment. (October 2019) - Zheng, T T; Li, Y W; Yang, P W; Chen, X L; Zheng, R; Miao, S H; Ji, H; Yin, H R
Abstract: The large-scale integration of wind power brings great challenges to power system secure and economic operation. In order to address this challenge, the variable speed pump storage hydropower plant (VS-PSHP) technology and demand response technology have addressed a lot attention. In this paper, the coordination of the thermal power generator, the wind power plant, the VS-PSHP and multi-type flexible loads are considered, and a day-ahead and real-time coordinated scheduling model are proposed. The proposed model can formulate the generation, contingency reserve and power distribution factor schedules simultaneously. Numerical simulation results indicate that the coordination of VS-PSHP and multi-type flexible loads can increase the system operation economic and mitigating the wind power curtailment. The results also show that the VS-PSHP is good at providing contingency reserve, and the participation of VS-PSHP can lead to a relatively lower total system operation cost compared to the participation of fixed speed pump storage hydropower plant (FS-PSHP).